2023
DOI: 10.1021/acs.energyfuels.3c02108
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Flower-like Ni3S2 on Nanoporous CuAg Alloy Heterostructure for Efficient Methanol Oxidation Reaction

Li Luo,
Shantang Liu,
Hanyu Li
et al.

Abstract: Direct methanol fuel cells (DMFCs) have captured increasing attention as promising renewable energy devices. The development of innovative, cost-effective electrocatalysts with superior performance for the methanol oxidation reaction (MOR) holds great significance in promoting DMFCs. In this study, a facile dealloying−electrodeposition method was employed to fabricate stereospecific Ni 3 S 2 nanoflowers on a three-dimensional nanoporous CuAg substrate (Ni 3 S 2 @CuAg) for accelerating MOR. The nanoporous CuAg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…They showed that the performance of LMO can be significantly improved by wrapping LMO with ion-selective reduced graphene oxide coatings. Luo et al 72 developed novel Ni 3 S 2 nanoflowers on a negatively charging 3D nanoporous CuAg substrate for catalytic oxidation of methanol in direct methanol fuel cells. The catalysts exhibit excellent catalytic performance owing to their preeminent conductivity, large specific surface area, and abundant active reaction sites.…”
Section: ■ Other Topicsmentioning
confidence: 99%
“…They showed that the performance of LMO can be significantly improved by wrapping LMO with ion-selective reduced graphene oxide coatings. Luo et al 72 developed novel Ni 3 S 2 nanoflowers on a negatively charging 3D nanoporous CuAg substrate for catalytic oxidation of methanol in direct methanol fuel cells. The catalysts exhibit excellent catalytic performance owing to their preeminent conductivity, large specific surface area, and abundant active reaction sites.…”
Section: ■ Other Topicsmentioning
confidence: 99%
“…A recent study by Xia and co-workers prepared flower-like Ni 3 S 2 on a CuAg alloy for effective methanol oxidation. They suggest that the outstanding MOR performance of Ni 3 S 2 @CuAg catalysts may be due to their abundant active reaction sites, large specific surface areas, and preeminent conductivity.…”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 99%